Penerapan Metode Fuzzy Mamdani Untuk Menentukan Stok Produk Herbal Berdasarkan Permintaan dan Penjualan - Nasyuha, Asyahri Hadi; Hutasuhut, Masyuni; Ramadhan, Mukhlis (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2019)
Sales is one of the activities undertaken by many people as a promising business field. Prediction of the number of items to be sold must be in accordance with stock at the store so that demand and sales can be fulfilled. Therefore, we need a system to find out the amount of stock of herbal products so they do not experience problems in determining stock in each month. By using the Fuzzy Mamdani method as an algorithm for solving the problem, and the criteria are changed in the form of weighting so that the system can do calculations that provide the speed of information in the form of a computerized system. The results of this study aim to apply the Mamdani fuzzy logic method in predicting the amount of herbal product stock based on sales data and the number of requests. Provides results in the form of information printed in a report containing order data for the number of subsequent stock orders